Pediatric trauma at a general hospital in Cali, Colombia (2016)
Background: Trauma is an important cause of morbidity and mortality in children. Blunt trauma is the most common type and falls and road traffic injuries (RTI) are the most frequent mechanisms. Methods: Secondary analysis of institutional data included within the Panamerican Society of Trauma Registry (STPITSDP). A total of 581 trauma patients younger than 18 years, hospitalized between 2012 and 2014, were included. Results: Blunt trauma (BT) (68%)was themost common type, and falls (42.5%) the most commonmechanism.Median age was: 14 years for penetrating trauma (PT), 8 years for BT, and 5.5 years for other types of trauma (OT). Of all patients, 8.1% had a Glasgow score b8, 9% had a Glasgow score of 8–13 and 81.1% had a Glasgow score higher than 14. Death occurred in 5.2% of patients: 83.3% as inpatients and 16.7% during initial management in the